Supporting teachers, supporting pupils : the emotions of teaching and learning - Wilson, Diana Fox (RoutledgeFalmer, 2004)
Drawing from the real-life experiences and perceptions of primary and secondary school teachers, this text documents their ideas on how they define their job, the difficulties they face and the support they need.